Curcumin improves LPS-induced preeclampsia-like phenotype in rat by inhibiting the TLR4 signaling pathway. (May 2016) - Gong, Ping; Liu, Mo; Hong, Guomin; Li, Yujing; Xue, Pingping; Zheng, Mingming; Wu, Mengfei; Shen, Li; Yang, Muyi; Diao, Zhenyu; Hu, Yali
Abstract: Introduction: Abnormal inflammation mediated by Toll-like receptor 4 (TLR4) signaling pathway contributes to preeclampsia (PE). Because curcumin can inhibit TLR4 signaling pathway, we investigated its effects on a PE rat model. Methods: Twenty-one pregnant rats were randomly divided into three groups: 1) seven rats were injected 0.5 μg/kg lipopolysaccharide (LPS) on gestational day (GD) 5 to create a PE model (LPS-treated group), 2) seven rats were injected with a similar dosage of LPS and further treated with curcumin (0.36 mg/kg) (LPS-curcumin-treated group), 3) seven rats received saline (control group). Blood pressure and urinary protein level were observed. Immunostaining and periodic acid-Schiff staining of placenta were conducted. TLR4 and downstream Nuclear Factor-κB (NF-κB) expressions of placenta were analyzed by Western blot and immunohistochemistry. IL-6 and MCP-1 in rat serum and placenta were determined by ELISA and qRT-PCR. Results: Compared to LPS-treated group, LPS-curcumin-treated group had decreased blood pressure and urinary protein level, similar to control group. Furthermore, deficient trophoblast invasion and spiral artery remodeling induced by LPS were improved by curcumin. Increased TLR4, NF-κB and IL-6, MCP-1 protein expressions in LPS-treated group were significantly decreased after curcumin administration. Discussion: Curcumin improves the PE-like phenotype in rat model by reducing abnormal inflammation related to TLR4 signaling pathway. Highlights: Curcumin ameliorated the hypertension and proteinuria of LPS-induced PE-like rats. Curcumin reversed LPS-induced shallow placental implantation. Curcumin prevented the LPS-induced PE-like rats from the renal injury. Curcumin suppressed overactivation of TLR4 signaling pathway in PE. Curcumin decreased excessive expression of inflammatory cytokines in PE.